Current research in earth sciences (Bulletin (Kansas Geological Survey))
Features the online edition of "Current Research in Earth Sciences," a publication of the Kansas Geological Survey. Notes that the articles focus on topics in earth science, with special emphasis on topics related to the midcontinent and Kansas geoscience. Offers information for authors.